Medico-legal Concerns of Common Sexual Dysfunction in Partners among Egyptian Sample - Heba Gamal Kotb; Walaa Abd el Hady Abd el Halim Abo-Zeid (Institute of Medico-legal Publications Pvt Ltd, 2021)
Erectile dysfunction (ED) is defined as affection of erection; it ranges from mild to severe degree while impotence is an absolute erectile dysfunction. ED affects physical and psychosocial health and has a significant impact on the quality of life of sufferers and their partners and families. It is a common disorder of men; however vaginismus is a recurrent or persistent involuntary spasm of the musculature of the outer third of the vagina that affects the quality of life and sexual satisfaction level. Objectives:The aim of the current study is to determine the real causes of common sexual dysfunction cases in Egyptian courts which the alleged male impotence and whether it is due to actual organic/vascular causes in male partner or vaginismus of the wife among Egyptian candidates.Subjects & Methods: a comparative study was taken over between the processing of the researched cases on the level of the legal authority and that of the private sector, based on laboratory and radiological investigations to diagnose the causes of apareunia of the couples subject to research in both spouses.Results: (96.7%)with incapability to perform the sexual intercourse were having the problem of vaginismuswhereas a very small percentage of the husbands were suffering from an organic reason with variable degrees of erectile dysfunction (3.3%).Conclusion & Recommendations: hymen is not a reliable sign to indicate male impotence, examination for vaginismus should be done in every case of alleged male impotence and examination for vaginismus.